Pengaruh Efektivitas Manajerial Kepala Sekolah dan Etos Kerja Terhadap Kinerja Guru Sekolah Dasar di Kecamatan Teluk Mutiara Kabupaten Alor - Magdalena Waang; Matin -; Masduki Ahmad (Peneliti.net, 2019)
Performance is the result of work and the progress that has been made by someone in their field of work. In achieving good result it needs to be supported by managerial effectiveness and a good work ethic between each person has an influence in improving teacher performance Elementary School at Kecamatan Teluk Mutiara Kabupater Alor.The population in this study amounted to 229 teachers, taking research samples using simple random sampling techniques using Slovin formula so that there were 146 teachers. Data is empirical data obtained from questionnaires that have been tested for validity and reliability. The collected data was anakyzed by descriptive analysis, then the hypothesis used path analysis.The results of the study show that there is a Principal Management Effectiveness that has a positive direct on performance. Work Ethics has a positive direct effect on performance. PPrincipal Management Effectiveness has a positive direct effect on the Work Ethic. The research implications are to improve the managerial effectiveness